(untitled) (Revija za sociologiju, 2019)
Prikaz knjige: Jadranka Švarc, Jasminka Lažnjak (eds): Innovation Culture in Crony Capitalism. Does Hofstede´s Model Matter?, Zagreb: Institute of Social Sciences Ivo Pilar, 2017, str. 236